2013
DOI: 10.1016/j.ygyno.2013.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Whole exome sequence analysis of serous borderline tumors of the ovary

Abstract: Objective Serous borderline tumor (SBT) is a unique histopathologic entity of the ovary, believed to be intermediate between benign cystadenoma and invasive low-grade serous carcinoma. While somatic mutations in the KRAS or BRAF, and rarely ERBB2, genes have been well characterized in SBTs, other genetic alterations have not been described. Toward a more comprehensive understanding of the molecular genetic architecture of SBTs, we undertook whole exome sequencing of this tumor type. Methods Following patholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 27 publications
(36 reference statements)
4
28
0
1
Order By: Relevance
“…Another study that examined the entire exome of serous BOTs for somatic genetic mutations showed similar results to low-grade serous carcinomas14. We should therefore consider hereditary risk, rather than somatic mutation.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Another study that examined the entire exome of serous BOTs for somatic genetic mutations showed similar results to low-grade serous carcinomas14. We should therefore consider hereditary risk, rather than somatic mutation.…”
Section: Discussionmentioning
confidence: 78%
“…A small proportion of BOT patients are known to have a somatic mutation 14. Another genetic test for BOT showed the possibility of an additional treatment based on gene sequencing results 15.…”
mentioning
confidence: 99%
“…The JCAD sequence is highly conserved in vertebrates from zebrafish to human (12), which indicates that the protein may have an important biological function. JCAD has been recently thought to be a novel candidate gene for a pathogenic role in serous borderline tumorigenesis (15). To our knowledge, its participation in oncogenesis has not been explored yet, nor has the role of JCAD in hepatic pathophysiology and carcinogenesis been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The results of exome sequencing of serous borderline tumors were recently reported. In addition to the previously reported oncogenic mutations of BRAF, FBXW7, and KIAA1462, novel gene mutations were reported [15]. Research groups from Johns Hopkins University and MD Anderson Cancer Center recently reported 2 new lines of evidence supporting the type I carcinogenesis pathway.…”
Section: Molecular-biological Characteristics Of Low-grade Serous Carmentioning
confidence: 95%